Social Action Of Student In Achieving Non-Academic Achievements In Interest And Talent-Based School - Wisudanto Wisudanto; Prawitra Thalib; Mohamad Nur Kholiq; Tri Vena Putri; Tri Veny Putri (Universitas Airlangga, 2022)
This article describes the social action of students' non-academic achievement. Student achievement in education is a measure of student success. Achievement has two categories, namely academic achievement and non-academic achievement. SMA Muhammadiyah 10 Surabaya has a gifted title. In accordance with this predicate, this school focuses on developing the potential interests and talents of students. This study uses social action theory by Max Weber in assessing the motivation for non-academic achievement goals. Researchers used qualitative methods through in-depth interviews and observation primary data, as well as secondary data through the development of student championship news on internet pages. The results showed that in achieving students' non-academic achievements, they achieved these goals through instrumental rational actions in the form of regular physical readiness exercises, value-oriented rational actions on aspects of spirituality, traditional actions on aspects of choosing extracurricular activities based on experience and advice from parents. , affective actions choose extracurricular activities because of feelings of pleasure and interest. The researcher hopes that this article can be a new contribution to society in the field of education and social affairs, especially the achievement of non-academic achievements which the community considers not a significant achievement for the future of students compared to academic achievement.